Computerized Accounting Systems and Financial Performance of Insurance Companies in Kenya - Ogola, Paul (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
Computerized accounting systems represent a technological evolution in financial management, replacing traditional manual accounting methods with automated processes. These systems leverage software and digital tools to streamline and organize various accounting functions within an organization. The study aims to address specific objectives, each focusing on different aspects of the computerized accounting systems. For instance, the study will look into how Kenyan insurance companies’ financial performance is affected by automated internal control systems. The purpose of the study is to evaluate the effects of computerized accounting systems on the financial performance of insurance companies in Kenya. Specific objectives include: To find out the effect of automated internal control systems on the financial performance of insurance companies in Kenya, to establish the effect of automated data processing on the financial performance of insurance companies in Kenya, to determine the effect of relational database management on the financial performance of insurance companies in Kenya and to examine the effect of automated reporting on the financial performance of insurance companies in Kenya. This study’s significance lies in its contribution to the understanding of factors that may improve the financial performance of insurance companies in Kenya. By exploring the impact of automated internal control systems, automated data processing, relational database management, and automated reporting systems, this study will provide valuable insights for insurance companies seeking to enhance their financial performance. The study will adopt a descriptive correlational research design as a result of the ability of the design to accurately portray the characteristic of a phenomena. The target population is composed of 4060 respondents from the 58 companies as given by the IRA (2020) report. The study shall then use stratified random sampling as well as purposive sampling to arrive at the required Sample. The study will then use Yamane (1964) formulae in calculating the required sample, sample size of 364 will be considered. Data collection tool will be questionnaires that are designed in a structured way to capture all the study objectives under review. The data collection process will be through the trained research assistants that will use a drop-and-pick method in administration of the questionnaires. Keywords: Computerized Accounting, Insurance Company, Financial Performance